2021
DOI: 10.3389/fncir.2021.701080
|View full text |Cite
|
Sign up to set email alerts
|

The Medial Septum as a Potential Target for Treating Brain Disorders Associated With Oscillopathies

Abstract: The medial septum (MS), as part of the basal forebrain, supports many physiological functions, from sensorimotor integration to cognition. With often reciprocal connections with a broad set of peers at all major divisions of the brain, the MS orchestrates oscillatory neuronal activities throughout the brain. These oscillations are critical in generating sensory and emotional salience, locomotion, maintaining mood, supporting innate anxiety, and governing learning and memory. Accumulating evidence points out th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 324 publications
(444 reference statements)
1
34
0
Order By: Relevance
“…Similar volumetric abnormalities have also been reported for the animal model used in this study [24,45]. In addition, the method also detected the medial septum, which plays a significant role in dopamine-related disorders such as schizophrenia [46,47] and addictions [48][49][50], which highlights the relevance of this structure in mental disorders. Regarding WM, the method found three well-defined brain areas, the frontal part of corpus callosum and WM tracts of the brainstem and the cerebellum [51,52].…”
Section: Discussionsupporting
confidence: 85%
“…Similar volumetric abnormalities have also been reported for the animal model used in this study [24,45]. In addition, the method also detected the medial septum, which plays a significant role in dopamine-related disorders such as schizophrenia [46,47] and addictions [48][49][50], which highlights the relevance of this structure in mental disorders. Regarding WM, the method found three well-defined brain areas, the frontal part of corpus callosum and WM tracts of the brainstem and the cerebellum [51,52].…”
Section: Discussionsupporting
confidence: 85%
“…MS neurons are under modulatory influences from several brain areas, including ascending cholinergic projections from the dorsolateral tegmental nucleus, serotonergic projections from the raphe nuclei, adrenergic inputs from the locus coeruleus (Takeuchi et al, 2021) and a dense projection from the brainstem, nucleus incertus (NI), an enigmatic structure involved in the control of contextual memories, locomotor speed, arousal, and stress responses (Ma et al, 2013(Ma et al, , 2017aSzőnyi et al, 2019;Lu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The septohippocampal loop with cholinergic synapses and cholinergic transmission function are important for neuroplasticity and neurodegeneration [54]. The literature revealed that BC has a high binding capacity toward AChE, and it attenuated cognitive dysfunction in a mice model of AD [42].…”
Section: Discussionmentioning
confidence: 99%